Omphalocele in Both Twins: Revealing Developmental Complexities: A Case Report - Gnanarathne, Sampath; Kariyawasam, Ayodhya (Gynecology Obstetrics & Reproductive Medicine, 2024)
Omphalocele is a rare congenital anomaly with eviscerated abdominal organs in the proximal segment of the umbilical cord covered by a membranous sac. This case presents omphalocele in both fetuses in a twin pregnancy, discussing the embryological basis, the importance of early detection, and effective management. A 34-year-old primigravida was confirmed to have dichorionic diamniotic twins at 6 weeks of gestation. At 14 weeks, a routine ultrasound revealed omphalocele in both fetuses, complicated by early amniotic rupture, following an uncomplicated preconception period. Omphalocele is a rare occurrence, simultaneously in a twin pregnancy. Among the various theories, this presentation favors the theory based on malformation of the ventral body wall. The exact embryological explanation is yet to be identified.